2005
DOI: 10.1039/b507258a
|View full text |Cite
|
Sign up to set email alerts
|

Photocontrol of ion-sensor performances in neutral-carrier-type ion sensors based on liquid-crystalline membranes

Abstract: Neutral-carrier-type ion-selective electrodes based on liquid-crystalline ion-sensing membranes containing an azobenzene derivative as the photosensitive chromophore show remarkable changes in their ion selectivity on photoirradiation, which is induced by the phase transition of the membranes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…These showed remarkable changes in their ion selectivity on irradiation, induced by the LC phase transition of the membranes. 207 Later examples focused on the control of hydrophobic/ hydrophilic balance brought about by photoisomerization. The swelling degree of a membrane in water made from an amphiphilic copolymer, poly(hydroxyethyl methacrylate) functionalized with azobenzene side groups, was found to decrease with UV irradiation but could be recovered to its original level by irradiating with visible light.…”
Section: Membranes-photo-regulated Permeabilitymentioning
confidence: 99%
“…These showed remarkable changes in their ion selectivity on irradiation, induced by the LC phase transition of the membranes. 207 Later examples focused on the control of hydrophobic/ hydrophilic balance brought about by photoisomerization. The swelling degree of a membrane in water made from an amphiphilic copolymer, poly(hydroxyethyl methacrylate) functionalized with azobenzene side groups, was found to decrease with UV irradiation but could be recovered to its original level by irradiating with visible light.…”
Section: Membranes-photo-regulated Permeabilitymentioning
confidence: 99%
“…Isomerization under UV light is also observed for other photo-chromic molecules like pyrimidine 231 , diarylethene 232 , viologen 233 and spiropyran 234 . Photo-responsive membranes can be obtained by preparing from monomers or polymers containing photo-chromic groups 235 , functionalizing membrane pores/surfaces with photo-responsive polymers 236 or embedding photo-switchable carriers into membranes 237 . A comprehensive review on photo-responsive polymeric membranes was recently done by Nicoletta et al 238 .…”
Section: Photo-responsementioning
confidence: 99%
“…We have previously reported that the ion selectivity of the ISEs based on low-molecular-weight liquid-crystalline compounds can be controlled by external stimulus: the changes of the ion selectivity were induced by the phase transition of the liquidcrystalline compounds used as the membrane solvents. [5][6][7][8] It was shown that the ion-sensor properties of ISEs depend remarkably on the orientation of neutral carriers in the ion-sensing membrane.…”
Section: Introductionmentioning
confidence: 99%